A Novel Technique of Arthroscopic‐Assisted Four‐Corner Fusion and Robot‐Assisted Fixation for Scaphoid Nonunion Advanced Collapse Wrist: A Single Case Study - XingShuai Gao; Rebecca Qian Ru Lim; Bo Liu (Orthopaedic Surgery, 2024)
Objective Scaphoid nonunion advanced collapse (SNAC) is a relatively common and debilitating wrist disorder yet its treatment remains challenging and controversial. We aim to describe a novel technique of a dual arthroscopic and robotic assisted four‐corner fusion (4CF) in the treatment of SNAC wrist. Methods In this study, we describe an original arthroscopic and robotic assisted 4CF, which is novel and currently unpublished in literature. The surgical approach included these predefined steps: arthroscopic resection of the scaphoid, radial styloid and of diseased cartilage between the capitate‐lunate joint and triquetrum‐hamate joint, correction of Dorsal Intercalated Segment Instability (DISI) deformity of the wrist and robotic assisted 4CF performed percutaneously with screws. Dynamic fluoroscopic imaging with the mini C‐arm was performed five times and the 3D scanning machine was used once. Results Our patient with SNAC II wrist was 57 years old at the time of initial presentation with a history of untreated traumatic wrist injury approximately 20 years ago. Regular wrist X‐rays were performed at the outpatient setting and a computed tomography (CT) of the wrist was performed at the third postoperative month to confirm bony union. The patient's wrist range of motion (ROM), grip strength, Visual Analog Scale (VAS) score, Quick Disabilities of Arm, Shoulder, and Hand (QuickDASH) score, Modified Mayo Wrist Score (MMWS), and Patient Rated Wrist Evaluation (PRWE) were also evaluated during short‐term follow‐up at 6 months. During the patient's review at 6 months, his VAS score was 0 with complete pain relief. His wrist flexion was 20° and wrist extension at 45°. His pronation‐supination was normal and comparable to his uninjured contralateral wrist. His operated wrist which was also his dominant hand had a grip strength of 22 kg as compared with 28 kg of the unaffected hand. He also had a Mayo Wrist Score of 85, QuickDASH score of 2.3 and PRWE of 6, and resumed his occupation as a clerk at 3 months. Conclusions This dual arthroscopic and robotic assisted 4CF is a novel surgical method worth considering in the treatment of SNAC II wrists. It is minimally invasive and allows for accurate placement of the screws in a single attempt. There was bony union by the third postoperative month as confirmed by CT imaging and excellent resolution of symptoms.